Tiny Spherical Robot with a Magnetic Field-Based Interference Detection and Prevention Framework - Mohamad Reda A. Refaai; S. Meenatchi; B. Ramesh; N. I. Haroon Rashid; N. B. Soni; Manikandan Ganesan (Advances in Materials Science and Engineering)
Spherical robots are a recent technique and have attracted attention due to their capacity to move at high speeds while maintaining great locomotion efficiency. Many research studies have been undertaken on spherical robots’ driving mechanisms, motion planning, and trajectory tracking systems, but only a few studies have been completed on their obstacle avoidance capacity. Its interfering prevention method was “hit and run” due to the existence of a sealed outer shell. This is convenient because of the spherical robots’ unique shape. It might cause major problems when the robots are light and small in size. A high-speed collision with a hard surface might harm the robot or the camera in portable spherical robots with onboard cameras. In this article, a magnetic field-based interference detection and prevention system for a tiny spherical robot has been established. The proximity sensor uses a passive magnetic field to detect ferromagnetic barriers by causing the magnetic field to be perturbed. It makes use of a passive magnetic field to keep the system small and power-effective. Because the suggested system can sense not only the existence of a ferromagnetic barrier but also its approaching direction, an intelligent avoidance behaviour may be developed by combining the detection information with the trajectory tracking technique. It amplifies the disturbance effectively and hence increases the detection performance. To improve obstacle detection performance, design optimization is carried out and specific avoidance techniques are designed.